PENGARUH MINAT BELAJAR DAN KEMAMPUAN BERKOMUNIKASI TERHADAP HASIL BELAJAR FIKIH SISWA MADRASAH IBTIDAIYAH NEGERI BAH KAPUL KOTA PEMATANG SIANTAR - Sumantri Sumantri (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to find out and to describe: (1) the effect of interest inlearning on student Jurisprudence learning outcomes, (2) the effect ofcommunication skills on student Jurisprudence learning outcomes, and (3)the influence of learning interest and the ability to communicate togetheron Jurisprudence learning outcomes students. This type of research isquantitative research with correlation research methods. The populationof this study was all students in class V MIN Bah Kapul, Pematang SiantarCity consisting of 2 classes with a total of 60 students. The instruments ofdata collection used were questionnaires and test results. Data analysistechniques used are correlation and regression. The research findingsshow: (1) a positive and significant relationship between interest inlearning and student learning outcomes with a correlation number of0.749 and a determinant coefficient of 0.561 with a regression line equation Ŷ = 44.72 + 0.50X1 (2) a positive relationship and significant between communication skills and learning outcomes with a correlation number of 0.391 and a determinant coefficient of 0.152 with regression line equation Ŷ = 56.67 + 0.27X2 (3) a positive and significant relationship between interest in learning and the ability to communicate together with results learning with a correlation number of 0.817 and a determinant coefficient of 0.667 with the regression line equation Ŷ = 36.27 + 0.483X1 + 0.196X2.